Estimating Geomagnetically Induced Currents in High‐Voltage Power Lines for the Territory of Kazakhstan - A. B. Andreyev; S. N. Mukasheva; V. I. Kapytin; O. I. Sokolova (Space Weather)
Abstract Extreme solar events, such as powerful solar flares are accompanied by the release of strong solar disturbances, such as coronal mass ejections (CMEs). The impact of CMEs on the Earth's magnetosphere causes geomagnetic storms, which trigger geomagnetic effects measurable in the ionosphere, upper atmosphere, and on and in the ground. During extreme cases, rapidly changing geomagnetic fields generate intense geomagnetically induced currents (GICs), which can cause dramatic effects on man‐made technological systems, including transmission lines and pipelines. In countries with large territories such as Kazakhstan, long power lines contribute to high values of induced currents during periods of extreme geoeffective solar events. It is of interest to estimate the values of GICs in an extensive network of power lines on the territory of Kazakhstan. However, there are no estimations of induced currents in power lines in Kazakhstan, and most estimation techniques are made difficult because of absence of field measurements of Earth conductivity. This study aims to model geoelectric fields on the surface of the Earth for Kazakhstan and to estimate the values of the GICs in 500 kV power lines. This study also compares between two methods for calculating induced voltages in power lines: one based on linear paths and the other based on curvilinear paths between substations of transmission power lines.